АНАЛІЗ ВПРОВАДЖЕННЯ ГЕНДЕРНОГО ПІДХОДУ В СИСТЕМУ ОСВІТИ В ПРАЦЯХ ПОЛЬСЬКИХ ДОСЛІДНИКІВ - Павловська, Вікторія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття присвячена аналізу праць польських дослідників щодо впровадження гендерного підходу в освітню систему Республіки Польща в постсоціалістичний період. Гендерний підхід в педагогіці орієнтований на формування гармонійних, вільних від гендерних стереотипів особистостей. У процесі аналізу польських науковців цікавлять питання подолання гендерної дискримінації в системі освіти; впровадження гендерної політики у вищих навчальних закладах; гендерні студії у контексті реформування освіти; перспективи подальшого застосування гендерного підходу в освіті. Статья посвящена анализу работ польских ученых по внедрению гендерного подхода в образовательную систему Польши. Гендерный подход в педагогике ориентирован на формирование гармоничных, свободных от гендерных стереотипов личностей. В процессе анализа польских ученых затрагивают вопросы преодоления гендерной дискриминации в системе образования; внедрения гендерной политики в высших учебных заведениях; гендерные исследования в контексте реформирования образования; перспективы дальнейшего применения гендерного подхода в образовании. The article deals with the analysis of the works of Polish researchers regarding the problems of gender approach implementation into Poland’s educational system. The results which are already gained in this field give the possibility to speak about the creation of a new theoretical branch in pedagogical sciences. Being a new approach in pedagogics, gender approach is oriented towards creating a harmonic personality which is free from gender stereotypes. Polish scientists consider different ways of overcoming gender discrimination in education. They also take interest in the problems of gender approach introduction in higher education, analyze the connection of gender studies with reforms in the educational system, and discuss the prospects of gender approach usage in pedagogics. The question of gender approach in the educational system is tightly related to the general situation in equality politics. Polish researchers tackle this problem as one of the necessary conditions for country’s integration into the European Union. Analyzing changes in education in the spirit of humanization, democratization and liberalization, the introduction of student-centered approach to training and education is considered to be the main goal of education system reforming.